Implementation Technology for Development of a Brand Communication in Company PT. XYZ - Nasution , Iskandar Mustofa; Bintaro, B.P. Kusumo; Kesumawati, Christien Setiya; Zahruddin, Muhamad; Nabila, Efa Ayu (Pandawan, 2022)
The study was conducted at Catering Service Company. The high competition of catering business requires the right brand communication strategy to communicate the uniqueness of the catering product in order to increase brand awareness. The purpose of this study is to define the right brand communication strategy by identifying external and internal factors, performing SWOT analysis, define segmentation, targeting and brand positioning. The research approach used is a qualitative and descriptive method with data collection using interviews and document studies. The results of the study shows that some competencies possessed by the company can be used as long-term competitive advantage. While other competencies are competitive equality because they also owned by competitors. These competitiveness should be communicated well to the target customers. Conclusion, Type of business for The Catering Company is Business to Business (B2B) for catering services to industrial (factory), training centers and events, and Business to Consumer (B2C) for wedding catering services. Marketing activities that will be carried out are integrated marketing communication (IMC) through Above the Line (ATL), Below the Line (BTL) and Through the Line (TTL). Brand Communication should be done with more focus and consistent, as well as need dedicated team to perform brand communication.